Reflexión: deforestación, contaminación y cambio económico en la pandemia (2021)
With the passage of time, deforestation, pollution, and the change of the global economic model in the pandemic is a relevant issue in the lives of everyone; especially today. The economic benefits from which people profit has thrown aside the environmental and economic consequences of their actions. The guidelines of this reflective article aims to show how common the practice of deforestation is in Colombia as well as its context globally. It will also demonstrate how deforestation will have repercussions on biodiversity in addition to the environmental consequences resulting from the damage caused withoutany kind of remediation such as prevention, caution, or the recovery of these areas. The development of energies based on the use of natural resources that generate pollution is very important and is directly responsible for a greater scale of change in the global economic model. This study allows the visualization of new perspectives of the reality in which man is involved. These radical changes in consumption and land use have created a situation that allows a reflection on how the future can be seen as a new opportunity to live in a better world, not for the present generations, but for our future generations.